Alemtuzumab following natalizumab in highly active paediatric-onset multiple sclerosis. Issue 3 (September 2019) - Margoni, Monica; Rinaldi, Francesca; Miante, Silvia; Franciotta, Silvia; Perini, Paola; Gallo, Paolo
We evaluated the occurrence of infusion-associated reactions, severe adverse events and no evidence of disease activity 3 status of a therapeutic course consisting of natalizumab followed by alemtuzumab in paediatric-onset multiple sclerosis. Five paediatric-onset multiple sclerosis (age range 16–17 years) were followed for a median of 3.9 years (interquartile range 3.1–5.0). At a natalizumab break (mean infusions 25.6 ± 1.3) patients were switched to alemtuzumab and completed the two therapy courses. Few mild/moderate infusion-associated reactions were observed during alemtuzumab infusion. No severe adverse events were detected. Natalizumab followed by alemtuzumab proved to be a well-tolerated therapeutic course in paediatric-onset multiple sclerosis. Moreover, paediatric-onset multiple sclerosis maintained the no evidence of disease activity 3 status throughout the follow-up.